As competências apontadas pelo fórum econômico mundial no contexto da indústria 4.0: um levantamento com profissionais da região de Sorocaba – SP - Fonseca, Juliana Carvalho; Silva, Danielly Cristina Candido da (Universidade Federal de São Carlos, 2021)
Industry 4.0 and the advancement of technologies are phenomena that are transforming the work settings of companies, promoting process automation, increased productivity, use of technologies such as big data, machine learning and the internet of things. These changes have a significant impact on work relationships, skills needed by professionals, the disappearance of some occupations and the creation of others. The purpose of this article is to understand whether professionals in the job market understand the skills they need to develop to remain competitive in this new context of the so-called 4th industrial revolution. The research method used is the Survey, and data collection was done through an electronic questionnaire containing multiple-choice and open-ended questions with short answers. The questionnaire was directed to professionals in the labor market who work in the region of São Paulo, Sorocaba and their surroundings. The data were compared with the 15 skills considered essential for the future of work according to the World Economic Forum. After analyzing the results, it is possible to conclude that young workers from the São Paulo - Sorocaba axis understand the importance and master all the competences raised by the World Economic Forum, except for the more technical competences such as use, monitoring and control of technologies, programming , systems analysis and evaluation. This gap raises the need for companies and governments to encourage the development of such technical skills considered important for the future of work. Keywords: Competencies. Industry 4.0. Job market.
The competencies pointed out by the world economic forum in the context of industry 4.0: a survey with professionals from the region of Sorocaba - SP. 2022
Keywords: Competências; Indústria 4.0; Mercado de trabalho; Competences; Industry 4.0; Job market; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS